2017
DOI: 10.1080/17470919.2017.1395765
|View full text |Cite
|
Sign up to set email alerts
|

Social dimension and complexity differentially influence brain responses during feedback processing

Abstract: Recent research emphasizes the importance of social factors during performance monitoring. Thus, the current study investigated the impact of social stimuli -such as communicative gestures- on feedback processing. Moreover, it addressed a shortcoming of previous studies, which failed to consider stimulus complexity as potential confounding factor. Twenty-four volunteers performed a time estimation task while their electroencephalogram was recorded. Either social complex, social non-complex, non-social complex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 75 publications
2
22
3
Order By: Relevance
“…Thus, the mere presentation of stimulus characteristics implying a social setting was enough to modulate neural correlates of feedback processing-most likely reflecting a bottom-up effect of the social stimuli. However, we demonstrated these results only in a western sample (Pfabigan, et al, 2019), which limits generalizability to this cultural group.…”
Section: Introductioncontrasting
confidence: 71%
See 4 more Smart Citations
“…Thus, the mere presentation of stimulus characteristics implying a social setting was enough to modulate neural correlates of feedback processing-most likely reflecting a bottom-up effect of the social stimuli. However, we demonstrated these results only in a western sample (Pfabigan, et al, 2019), which limits generalizability to this cultural group.…”
Section: Introductioncontrasting
confidence: 71%
“…Several recent studies have demonstrated that early brain responses reflecting the activity of our performance monitoring system are sensitive to physical stimulus properties of external feedback stimuli. While Liu, Nelson, Bernat, & Gehring (2014) and Pfabigan, Sailer, & Lamm (2015) showed that perceptual properties such as similarity of perceptual features and stimulus size differentially influence performance monitoring correlates, we demonstrated that social versus nonsocial stimulus characteristics were reflected in early brain responses to feedback stimuli (Pfabigan, Gittenberger, & Lamm, 2019). The authors reported that social (vs. nonsocial) and complex (vs. noncomplex) feedback stimuli enhanced processing of feedback information at several successive stages.…”
Section: Introductionmentioning
confidence: 42%
See 3 more Smart Citations